Analyzing human behavior in cyberspace - Yan, Zheng 1958- (IGI Global, Disseminator of Knowledge, 2019)
"This book explores new ideas and research findings related to psychological aspects and serves as a vehicle for promoting techniques and methodologies derived from rigorous research and practices that use psychological and cognitive principles to design and develop cyber learning"...
Includes bibliographical references
Keywords: Online social networks -- Psychological aspects; Electronic commerce; Computer crimes; Consumer behavior; Computer users -- Psychology; Social Media; Cyber-Mobbing; Electronic Commerce; Aufsatzsammlung